Optimalisasi Hasil Produksi Menggunakan Metode Khun Tucker - Dhurun Muhdi Zayyan; Ahmad Isro'il (Jurnal Matematika dan Sains (JMS), 2023)
The purpose of this study was to determine the maximum profit in Islah Convection. This study used the Kuhn-tucker method. The Kuhn-tucker method is a method used to determine the optimum value of a function with an inequality constraint. The steps of this research are forming decision variables, forming objective functions, forming constraint functions, forming mathematical models with linear programming, solving optimization problems using the Kuhn-tucker method, and drawing conclusions. The results of the completion of this study obtained a maximum profit of Rp. 273,562,325 in the production of 4 types of clothes, which include 200 units of male school uniform, 200 units of female school uniform, 60 units of alma mater coat, and 30 units of katelpak. . Based on the results of the optimization, it can be concluded that the profit of clothing production in Islah Convection is optimal